Меджибіж: нижньопалеолітична пам’ятка на схід від Карпат - Степанчук, В.М.; Рижов, С.М.; Погорілець, О.Г. (Археологія, 2012)
Охарактеризовано нижньопалеолітичне місцезнаходження на лівому березі р. Південний Буг біля смт Меджибіж Летичівського р-ну Хмельницької обл., вік якого підтверджений біостратиграфічними та археологічними даними. Местонахождение Меджибож известно среди палеонтологов и геологов уже около 100 лет. Впервые на наличие здесь каменных изделий, которые, вероятно, принадлежали древнему человеку, обратил внимание геолог и археолог-любитель В.К. Пясецкий, что проигнорировали палеолитоведы. Таким образом, с начала ХХ в. и до недавнего времени здесь время от времени проводились лишь геологические, палеонтологические и разведочные археологические работы (В.К. Пясецкий, Л.И. Рековец). The locality of Medzhybizh is well known among palaeontologists and geologists for about 100 years. It was V.K. Pyasetski, a geologist and an amateur archaeologist, who first drew attention to stone artifacts which apparently were products of ancient man activity, but this assumption was ignored by professional archaeologists studying Palaeolithic. Thus, since the beginning of the 20th c. until recently only geological, paleontological and archaeological prospecting (V.K. Pyasetskyi; L.I. Reko vets) were conducted from time to time.